Attempts of protection against Boophilus microplus ticks in calves immunized with antigens .ofHyalomma marginatum isaaci - Ponnudurai, G; John, Lalitha; Harikrishnan, T J (The Indian Journal of Animal Sciences, 2011)
Crossbred calves, immunized with 4mg ofpurified midgut antigen of Hyalomma.marginatum isaaci, were challenged after 7 days of first booster with 100 Boophilus mjcroplus larvae. The larval and nymphal stages fed normally and moulted to become adults. However, mortality was noticed in adult female ticks (242.-29%) fed on immunized calves. The reproductive performances ofsurvived ticks were not affected. Â